Young people in care and criminal behaviour - Fitzpatrick, Claire, 1976- (Jessica Kingsley Publishers, 2006)
Society holds a mistaken perception that links children in public care with criminal activity. This book addresses the lack of evidence supporting this potentially damaging assumption, analysing past research, critically examining current policy and combining theoretical insights from the disciplines of childcare and criminology.
Keywords: Youth -- Institutional care -- Great Britain.; Foster children -- Great Britain.; Criminal behavior, Prediction of -- Great Britain.; Juvenile delinquency -- Great Britain.; Jeunesse -- Soins en institutions -- Grande-Bretagne.; Délinquance juvénile -- Grande-Bretagne.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Criminal behavior, Prediction of; Foster children; Juvenile delinquency; Youth -- Institutional care; Great Britain